Etude rétrospective sur le Retentissement de la Chimiothérapie sur l’Etat Nutritionnel des Patients Cancéreux dans le Service d’Oncologie de l’EPH de Laghouat - GARADI Sabrine Inssaf (Université Amar Telidji de Laghouat Faculté de Médecine, 2021)
A state of malnutrition is so commonly associated with tumor disease that it is often considered an integral part of the evolution of cancers. Materials and methods This is a retrospective monocentric study carried out in the Medical Oncology department of the PHE of Laghouat. Patients with cancer and followed in this service between October 4, 2020 and November 26, 2020 have been included. The main objective was to study the impact of chemotherapy on the nutritional status of cancer patients by assessing the nutritional status and quantifying its anthropometric and biological parameters. Malnutrition is defined as weight loss > 5% in one month or > 10% in six months and/or body mass index ≤ 18,5 kg/m² and/or albuminemia 30 g/L in adult patients aged < 70 and by weight loss 5% in one month or 10% in six months and/or body mass index ≤ 21 kg/m² and/or albuminemia 35 g/L in patients aged ≥70. Results This study included 123 patients with a sex ratio of 0.6 and an average age of 51.81±14.33 years who were sectioned into 2 groups: undernutrition with a weight loss greater than 5% of usual weight and or BMI 18, 5kg/m² and or albuminemia 30g/L (in 70-year-old patients) and or BMI 21 kg/m² and or albuminemia 35g/L (in 70-year-old patients) (n=16, 13%) and those without malnutrition (n=107, 87%). Men accounted for 34.6% of the not undernourished population and 56.3% of the malnourished population. The weight change in the undernourished group was on average - 1.12%±5.4 with 30.1% of undernourished people have PDP>5% and 81.26% were on chemotherapy. The mean BMI of the undernourished population is 18.63kg/m² 3.98 and the mean albumin is 35.65 3.68 g/L in the undernourished population. Discussion and conclusion The undernutrition of cancer patients is common and associated with less benefit from chemotherapy and a derogatory prognosis, this has been demonstrated in our study among patients suffering from the adverse effects of chemotherapy, especially digestive side effects.
133 p.